THE EFFECT OF JOB TRAINING PROGRAMS AND JOB MARKET INFORMATION ON THE JOB READINESS OF VOCATIONAL SCHOOL GRADUATES: A HUMAN RESOURCE MANAGEMENT PERSPECTIVE - Nova Karlina; Kosasih (RADJA PUBLIKA, 2025)
This study aims to examine the influence of job training programs and the provision of job market information on the job readiness of Vocational High School (SMK) graduates from a human resource management perspective. Using a quantitative approach with a survey method allowed researchers to collect data from 200 SMK graduates in a specific region who had participated in job training and had access to job market information. A valid and reliable questionnaire was used as the data collection instrument and was analyzed using multiple linear regression to test the influence of each independent variable on the dependent variable, namely job readiness. The results showed that job training programs and job market information significantly and positively influenced the job readiness of SMK graduates. This finding confirms that providing training that is in line with industry needs and increasing access to job market information are important factors in improving graduates' competence and competitiveness in the workforce. This study provides strategic implications for schools, the government, and industry stakeholders in developing more effective human resource development policies and programs that are relevant to current and future job market needs